Ανάπτυξη Clustering Αλγορίθμων για Διάχυση Πληροφορίας σε Δίκτυα Αυτοκινούμενων - (:unkn) unknown (My University, 2021)
Η διάχυση πληροφορίας σε δίκτυα οχημάτων είναι ιδιαίτερα σημαντική στην σημερινή πραγματικότητα, καθώς μπορεί να αποτελέσει χρήσιμο εργαλείο στην επίλυση πολλαπλών προβλημάτων, όπως η επαναφορά της ορθής λειτουργίας ενός οδικού συστήματος σε περίπτωση μποτιλιαρίσματος. Σε ένα κινητό δίκτυο οχημάτων η κατανεμημένη διάχυση πληροφορίας αποτελεί κάτι ιδιαίτερα πολύπλοκο καθώς τα δίκτυα αυτά διαφέρουν από τα παραδοσιακά κινητά δίκτυα που έχουν προμελετηθεί. Στα δίκτυα οχημάτων, η επιτυχής διάχυση της πληροφορίας, δεν προϋποθέτει την επιτυχή μετάδοση της στα δίκτυα αυτά, αλλά την μετάδοση της πληροφορίας αυτής στο υποσύνολο του δικτύου που θα του είναι χρήσιμη. Στόχος της παρούσας διπλωματικής είναι η αποδοτική διάχυση πληροφορίας σε δίκτυα αυτοκινούμενων με την χρήση αλγόριθμων συσταδοποίησης (Clustering).

Vehicular Ad Hoc Networks (VANETs) have the potential to become viable to Intelligent Transportation System (ITS) real-world applications. Vehicles’ high mobility along with real-world application scalability are some of the main challenges in this network environment. The various mobility- based characteristics can be exploited by forming clusters of vehicles with similar attributes within the network. Clustering in VANET environments is an approach that converts the network structure from flat into hierarchical by dividing the network into groups of vehicles, called clusters. One of the main requirements for effective VANET clustering is stability given the dynamicity of the environment. This paper presents a multi-head clustering algorithm that utilizes mobility-based metrics to form clusters in a vehicular network. The proposed algorithm assumes that each vehicle can be a member of multiple clusters, thus creating stable clusters that are robust in this environment. Several simulations are carried out to test the algorithm’s effectiveness under different scenarios. The proposed algorithm is also compared against a previously presented algorithm, called Double-Head Clustering Algorithm. The performance evaluation is based on metrics regarding the clusters’ lifetime. The results outline that the presented algorithm outperforms the clustering algorithm of the bibliography both in cluster stability and cluster size.
Development of Clustering Algorithms for Information Dissemination in Vehicular Networks
Keywords: δίκτυα, πληροφορική, δίκτυα αυτοκινούμενων, ad-hoc, συσταδοποίηση; clustering,ad-hpc networks, VANETS, vehicular clustering